Smart health monitoring system based on internet of things with big data analytics and wireless networks - Florence, S; Shyamala Kumari, C; LeemaPriyadharshini, L (International Journal of Engineering and Technology, 2018)
The use of mobile application technologies and smart devices in the health sector has improved a lot. In this sense health monitoring has evolved using Internet of Things. Nowadays the food habits are changed because of our machine life. This paper mainly focuses on the problems occurring related to health because of food habits. This paper gives the idea for solving this problem by collecting the attributes from the human body. The attributes like cholesterol, calories, glucose, pulse, weight, Body Mass Index, water level, temperature are to be collected from the person by fixing the wearable sensor devices in the human body. After getting these attributes the analysis should be done with the existing database for giving the food recommendations. The food intake level is analyzed for providing health factors. The aim of the paper is to provide the architecture for healthy food recommendations to the persons using sensor data to the person’s mobile application.